Evidências de disseminação de conteúdo no Telegram durante o ataque aos órgãos públicos brasileiros em 2023 - Venâncio, Otávio R.; Gonçalves, Gabriel H. S.; Ferreira, Carlos H. G.; Silva, Ana Paula C. da (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2024)
Given the increasing importance of instant messaging apps in the dissemination of information, this study investigates coordination patterns in user groups on the Telegram in post-2022 election Brazil. Text messages shared in approximately 270 politically oriented groups during the first two weeks of January 2023 were analyzed using a methodology that includes media-centric network modeling, backbone extraction techniques, and community detection algorithms. Our results reveal evidence of user coordination in promoting antidemocratic content, demonstrating how these communities are capable of efficiently disseminating information on a large scale. Specifically, we observed significant activity related to the attack on Brazilian public institutions, including the government, Supreme Federal Court (STF), Senate, and Congress.